Prediction of seasonal population dynamics of Grapholita molesta (Busck) and Adoxophyes orana (Fischer von Röslerstamm) in peach orchards using sex pheromone trap and degree-days and its implications in pest management - Ma, Aihong; Zhang, He; Ran, Hongfan; Yang, Xiaofan; Hao, Jianbo; Zhang, Jianfeng; Li, Huijie; Yu, Zihang; Wang, Xiaoxi; He, Xiong Zhao; Li, Jiancheng (Frontiers in Agronomy, 2023)
The successful management of lepidopteran moths in orchards usually depends on the precise forecast of adult activity. However, the seasonal phenology of moths varies between crop cultivars and years, making it difficult to schedule the control measures. Here, we monitored male flight activity of oriental fruit moth Grapholita molesta and summer fruit tortrix moth Adoxophyes orana by using sex pheromone traps in peach orchards of three different cultivars for three successive years. We developed a logistic multiple-peaks model to fit data and then calculated degree-days (DD) required for male activity and neonate emergency. Results show that G. molesta and A. orana males had 4–5 and 3 flight peaks per year, respectively. The seasonal phenology of G. molesta or A. orana was quite stable with an identical timing of each flight peak between cultivars in a year. The flight activity was usually higher in the second and third peaks for both moths, with a higher cumulative number of G. molesta males captured than that of A. orana. Compared to A. orana, G. molesta emerged early in spring and required lower degree-days to reach the subsequent flight peaks and for neonate emergency. Our results suggest that to decline the possibility of outbreaks of moths during the growing seasons, pheromone traps should be scheduled in April with a cumulative DD between 49.6 and 207.1 for G. molesta and in mid-May–early June with a cumulative DD between 450.4 and 866.7 for A. orana, aiming to trap the newly emerged male adults or disrupting female mating success of overwintered moths in orchards. Based on the thermal requirement for egg hatching (i.e., 79.4 DD for G. molesta and 90.0 DD for A. orana), insecticide treatments would be applied in late-April–early May and late May–early June to reduce the field population density of neonates of G. molesta and A. orana, respectively, to reduce fruit damage in orchards. Furthermore, pheromone traps set up in late July–early August (573.8–1025.2 DD) for G. molesta and in mid-September (1539.7–1788.9 DD) for A. orana may suppress overwintering populations and thus decrease pest infestation in next year.